Mozambican adolescents' perspectives on the academic procrastination process. (April 2018) - Fulano, Celso; Cunha, Jennifer; Núñez, José Carlos; Pereira, Beatriz; Rosário, Pedro
The current study explored Mozambican adolescents' perspectives of the process of academic procrastination, focusing on three key aspects: Type of tasks where youth usually procrastinate, antecedents, and the perceived consequences. Twenty-four adolescents from a pool of 300 (11th and 12th graders) reported high levels of procrastination and were selected to be interviewed. Data were analysed using content analysis. Overall, the findings showed that perceived lack of content knowledge can be the antecedent of procrastination behaviors, particularly when it comes to homework. These findings may help teachers and school administrators create a better school environment that promotes learning engagement and inhibits procrastination.